Assessment of ultraviolet (UV) radiation from technical sources - Chadyšienė, Renata; Girgždys, Aloyzas (Journal of Environmental Engineering and Landscape Management, 2009)
The paper presents the assessment of ultraviolet radiation from technical sources. It has been determined that the intensity of UVA radiation is about 10 times higher than the intensity of radiation of UVB. It has been investigated that the intensity of UV radiation during the welding process nonlinearly depends on the strength of the current, namely, if the strength of the current is reduced by 60%, the intensity of UV radiation is reduced by 20%, it also depends on the distance from the source, namely, if the distance is increased 10 times, the intensity of UV radiation is reduced about 25 times. The dose of UVA and UVB radiation from various resources is calculated. Comparison with the minimum erythema dose is submitted. It has been obtained that when the strength of the current is 315 A, the UV radiation dose exceeds 1 MED, namely, UVA ∼ 3000, UVB ∼300 times. After having carried out the experiment it has been found that the UV radiation emitted from a welder comprises about 80% of UVA, and about 20% of UVB. The results of investigation made in a solarium show that UV radiation from lamps comprises 98% of UVA radiation and 2% – of UVB radiation, while in the Sun rays reaching the Earth UV radiation comprises 96% of UVA and 4% of UVB. Dirbtinių šaltinių skleidžiamos UVA ir UVB spinduliuotės įvertinimas Santrauka. Darbe radiometriniais metodais nustatyti ir įvertinti dirbtinių šaltinių skleidžiamos ultravioletinės alfa ir beta spinduliuotės (UVA ir UVB) intensyvumo pokyčiai ir apskaičiuota įvairių šaltinių sukuriama UVA ir UVB spinduliuotės dozė. Nustatyta, kad suvirinimo proceso metu skleidžiamos UV spinduliuotės intensyvumas priklauso nuo šaltinio intensyvumo (sumažinus šaltinio intensyvumą apie 60 %, UV spinduliuotės intensyvumas sumažėja apie 20 %) bei nuo atstumo nuo šaltinio (padidinus atstumą 10 kartų UV spinduliuotės intensyvumas sumažėja apie 25 kartus). Įvairių šaltinių sukuriama UVA ir UVB spinduliuotės dozė palyginama su minimalia eritemine doze. Gauta, kad suvirinimo metu, esant 315 A elektros srovės stipriui, UVA spinduliuotės dozė 1 MED viršija apie 3000, UVB 300 kartų. Nustatyta, kad apie 80 % iš suvirinimo aparato skleidžiamos UV spinduliuotės yra UVA, o apie 20 % – UVB. 98 % soliariumo lempų skleidžiamos UV spinduliuotės yra UVA ir 2 % – UVB, gi iš Žemę pasiekiančios Saulės UV spinduliuotės 96 % yra UVA ir 4 % UVB. Reikšminiai žodžiai: UVA spinduliuotė, UVB spinduliuotė, spinduliuotės intensyvumas, technogeniniai šaltiniai, UV dozė, minimali eriteminė dozė (MED). Определение УФА- И УФБ-излучений от техногенных источников Резюме. Радиометрическими методами определены изменения УФА- и УФБ-излучений некоторых техногенных источников, а также рассчитана доза УФА- и УФБ-излучений этих источников. Установлено, что в среднем интенсивность УФА-излучения в 10 раз сильнее интенсивности УФБ-излучения. Установлено также, что в процессе сварки интенсивность испускаемого УФ-излучения зависит от интенсивности источника: при снижении интенсивности источника на 60% интенсивность УФ-излучения снижается приблизительно на 20%; при увеличении расстояния от места сварки в 10 раз интенсивность УФ-излучения снижается приблизительно в 25 раз. Рассчитана доза УФАи УФБ-излучений, создаваемая различными техногенными источниками. Представлено ее сравнение с минимальной эритемной дозой. Получено, что во время сварки при силе электрического тока 315 А доза УФА-излучения превышает 1 МЭД в 3000 раз, а УФБ-излучения – в 300 раз. Экспериментальными исследованиями получено, что испускаемое при сварке УФ излучение на 80% состоит из УФА-излучения и на 20% – из УФБ-излучения. В соляриуме, где был проведен эксперимент, УФ-излучение ламп состоит на 98% из УФА лучей и на 2% из УФБ лучей. Для сравнения: околоземное УФ-излучение Солнца в Литве состоит в среднем на 96% из УФА лучей и на 4% из УФБ лучей. Ключевые слова: УФА-излучение, УФБ-излучение, интенсивность излучения, техногенные источники, УФ доза, минимальная эритемная доза. First Published Online: 14 Oct 2010